Une approche diachronique des TMS : usage de données quantitatives dans une grande entreprise - Céline Mardon; Willy Buchmann; Serge Volkoff (Perspectives Interdisciplinaires sur le Travail et la Santé, 2013)
This article is based on the quantitative part of an ergonomics study whose goal it was to understand how work modifications increased or limited the occurrence and persistence of musculoskeletal disorders (MSD) among operators in an aeronautical industrial group, using a diachronic approach to the empirical evidence. A monitoring system (Evrest), based on the systematic collection of quantitative data from the operators, allowed us to relate the operators’ past and present MSD risk factors to their musculoskeletal health. Based on these relations, we explored possible worker strategies, wear and tear phenomena, and sheltering processes developed for workers suffering from serious joint diseases. With regard to the last two elements, the analysis was based on the study of "constraint sequences" and "constraint accumulation." The definition of constraint was based on a combination of questions about physical constraints, time pressure, and opportunities to choose how to do one’s work.